ACADEMIC CULTURE AS A COMPOSITION OF NATIONAL INNOVATION SECURITY - Олена Семеног (Ivan Ziaziun Institute of Pedagogical Education and Adult Education of the NAES of Ukraine, 2020)
The article describes the essence and content of academic culture as a significant component of national innovation security. The semantic and terminological analysis of the key concepts of the research like «national security», «human security», «human security of humanity», «human capital» were carried out. The concept of «innovative security» is described as a stable, effective provision of country's innovations in the economy, creation of conditions for modernization of industries, development of priority areas of fundamental and applied scientific research, technical and technological developments that ensure the competitiveness of the country. It was proved that main features of academic culture are the culture of study at the university, ethical values, traditions, norms, rules for conducting scientific research; scientific linguistic culture, professional subculture of the scientific community; social, moral responsibility for the process and results of the research which is formed in the cultural and educational space of higher education institution. The cultural and educational space of the university is described as a component of the development of human capital and one of the factors of national innovation safety. It is noted that universities must clearly show the values of educational services, be centers of academic culture, act on the principles of academic freedom, public responsibility, respect for human dignity and support adherence to academic integrity in research activities. The formation of the researcher's academic culture in the conditions of the university's cultural and educational space is defined as a complex, multidimensional, phased process of qualitative changes in the psychological sphere of the individual, taking into account the main provisions of the theory of activity, intercultural communication; the ideas of a humanistic, acmeological paradigm; concept of continuous pedagogical education.